Pengaruh Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada CV Dharmala Putra - Putri Apriyani; Henny Armaniah (CV. ULIL ALBAB CORP, 2024)
The aim of this research is to find out how service quality and customer satisfaction influence customer loyalty. This research was conducted at CV Dharmala Putra which operates in the electronic trading sector, especially shaving equipment with a product called kemei. This research uses quantitative data using multiple linear regression methods through observation, questionnaires, interviews and literature study. The data used is primary data and secondary data. Primary data consists of interviews, questionnaires, observations and pre-surveys. Secondary data includes interviews, documentation, sales data, video conversations and customer data. The sampling technique uses non-probability sampling techniques for sampling and population. The technique uses saturated sampling. to select samples from all CV Dharmala Putra customer data as the population for this study. The results of this research are that service quality partially has a positive and significant effect on customer loyalty so that Ho is rejected and Ha1 is accepted, customer satisfaction partially has a positive and significant effect on customer loyalty. Then simultaneously service quality and customer satisfaction have a positive and significant effect.